A photoaffinity probe that targets folate-binding proteins. (15th May 2021) - Takamura, Akihiro; Thuy-Boun, Peter S.; Kitamura, Seiya; Han, Zhen; Wolan, Dennis W.
Graphical abstract: Abstract: Folate and related derivatives are essential small molecules required for survival. Of significant interest is the biological role and necessity of folate in the crosstalk between commensal organisms and their respective hosts, including the tremendously complex human distal gut microbiome. Here, we designed a folate-based probe consisting of a photo-crosslinker to detect and quantitate folate-binding proteins from proteomic samples. We demonstrate the selectivity of our probe for the well-established human folate-binding protein dihydrofolate reductase and show no promiscuous labeling occurs with human caspase-3 or bovine serum albumin, which served as negative controls. Affinity-based enrichment of folate-binding proteins from an E. coli lysate in combination with mass spectrometry proteomics verified the ability of our probe to isolate low-abundance folate-dependent proteins. We envision that our probe will serve as a tool to elucidate the roles of commensal microbial folate-binding proteins in health and microbiome-related diseases.